Islamic Religious Education in a Minority Context: Identity Negotiation, Pedagogical Adaptation, and Religious Moderation Practices - Respi Pradina Vika; Muhammad Ahalla Tsauro Tsauro; Hamdhan Djainudin Djainudin (Dialogium: Journal of Islamic Studies, 2026)
Islamic Religious Education (IRE) in demographic minority regions faces complex challenges in balancing the strengthening of faith (aqidah) with the necessity of social adaptation amidst the dominance of other religious cultures. This study aims to analyze how IRE at SMA Negeri 1 Komodo, East Nusa Tenggara, serves as an arena for identity negotiation and pedagogical adaptation for minority Muslim students. This research employs a qualitative approach with a case study design, where data were collected through participant observation, in-depth interviews, and document analysis. The results indicate that minority status does not drive Muslim students toward self-isolation; rather, it fosters the formation of a fluid and confident identity in which the school functions as a "contact zone" for social negotiation. IRE teachers act as "cultural brokers" who undertake pedagogical adaptations by shifting from a textual approach toward value transmission through the "hidden curriculum" and extracurricular activities. The findings also emphasize that religious moderation in this setting manifests as "lived religion," emerging organically through the support of the social ecosystem and the local wisdom of the Labuan Bajo community. This study concludes that IRE in minority settings is capable of transforming from a dogmatic approach into a socio-constructivist approach that effectively builds social cohesion.